Nursing Students' Stress And Health Study On Nurse Engagement And Wellness (Journal of Pharmaceutical Negative Results, 2022)
Nurses have a significant role in healthcare systems, being the world's largest group of healthcare professionals. Nurses at hospitals can directly influence patient outcomes, safety, and satisfaction because of their close patient contact. Chronic psychosocial stress, however, can impair nurses' ability to deliver high-quality care by raising the risk of medical error and decreasing job satisfaction (Elfering, Semmer, & Grebner, 2006). (Roberts & Grubb, 2014). Long shifts, arduous job duties, constantly changing jobs, and—in some cases—hostility among coworkers all contribute to stress among nurses (Moustaka & Constantinidis, 2010; Oyeleye, Hanson, O'Connor, & Dunn, 2013). This persistent and regular stress exposure can lead to biological deterioration (also known as allostatic load), which raises people's risk of developing various illnesses and cognitive loss (McEwen, 1998).1Workplace stress among nurses has been linked to health issues like obesity, cardiovascular disease, and type 2 diabetes, as well as a higher risk of depression, burnout, and suicidality (McNeely, 2005). (Karasek & Theorell, 1990). Chronic stress can impair cognitive abilities such as memory and attention, which increases the likelihood of medication errors, failure to notice life-threatening symptoms, and other essential patient safety issues among nurses (Karimi, AdelMehraban, & Moeini, 2018; McEwen, 1998). Stress also increases attrition (i.e., leaving one's current job) and turnover (i.e., leaving nursing), particularly among new nurses (Blythe et al., 2008; Rudman, Omne-Ponten, Wallin, & Gustavsson, 2010). As a result, understaffed nursing teams become less effective and productive (Newman, Maylor, & Chansarkar, 2001; Squillace, Bercovitz, Rosenoff, & Remsburg, 2008).2Stress seems to be especially dangerous for new nurses as they move from nursing school to the workplace (Fink, Krugman, Casey, & Goode, 2008). 34% of nurses change professions within the first two years of graduating, with stress being a common reason (Kovner, Brewer, Fatehi, & Jun 2014; Kovner & Djukic, 2009). Studies have also shown that occupations like nursing that demand constant human contact are vulnerable to stress and burnout even before employment (Moreira & Furegato, 2013; Rudman & Gustavsson, 2012). According to Pulido-Martos, Augusto-Landa, and Lopez-Zafra (2012), nursing students, for instance, suffer stresses specific to the nursing curriculum, such as clinical training, as well as stress from situations that are typical of college students, including examination anxiety (Turner & McCarthy, 2017). Students who must juggle family, work, and other obligations with academic requirements may experience extreme stress. Little is currently known regarding the relationship between nursing school stress and vulnerability to workplace stress. The performance and wellness of new nurses and their patients' health may be improved by having a better understanding of how students deal with stress.